Barron's E-Z trigonometry - Downing, Douglas (E-Z series., 2010)
From the Publisher: This self-instruction book explains angles and triangles, and demonstrates the solutions to right triangle problems. Chapters that follow deal with trigonometric functions of sine, cosine, and tangent, radian measures, Pythagorean and other trigonometric identities, graphs of trigonometric functions, waves, polar coordinates, complex numbers, conic sections, spherical trigonometry, polynomial approximation for sin x and cos x, and more. Exercises follow every chapter with answers given at the back of the book.